Minimasi Waste Produk Side Chair di UD. Mustika Agung dengan Menggunakan Metode Waste Relationship Matrix - Wardana, Bima Triaji; Hendarawan, Aloysius Tommy; Khoiri, Halwa Annisa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
UD. Mustika Agung is a company that focuses on the production of side chairs in East Java. Defects were found in the production process, namely several cracked joints due to wood that was not fully dried, and inventory, namely there were side chairs stacked on side chairs caused by the queuing process for finishing. UD. Mustika Agung seeks to reduce waste in the production of side chairs by implementing the concept of lean manufacturing to minimize existing waste. One of the tools to minimize the concept of lean manufacturing is the Waste Relationship Matrix (WRM) which functions to identify waste that occurs in the company. The two largest wastes were found, namely defects with a score of 32 and inventory with a score of 26. The proposed improvements are to replace the oven machine with a more modern one and add employees